An uncertain glory : India and its contradictions - Drèze, Jean; Sen, Amartya, 1933- (Princeton University Press, 2013)
When India became independent in 1947 after two centuries of colonial rule, it immediately adopted a firmly democratic political system, with multiple parties, freedom of speech, and extensive political rights. Maintaining rapid as well as environmentally sustainable growth remains an important and achievable goal for India. Two of India's leading economists argue that the country's main problems lie in the lack of attention paid to the essential needs of the people, especially of the poor, and often of women. In the long run, even the feasibility of high economic growth is threatened by the underdevelopment of social and physical infrastructure and the neglect of human capabilities.